Harm to others outweighs harm to self in moral decision making - Crockett, Molly J.; Kurth-Nelson, Zeb; Siegel, Jenifer Z.; Dayan, Peter; Dolan, Raymond J. (Proceedings of the National Academy of Sciences - PNAS, 2014)
Significance Concern for the welfare of others is a key component of moral decision making and is disturbed in antisocial and criminal behavior. However, little is known about how people evaluate the costs of others’ suffering. Past studies have examined people’s judgments in hypothetical scenarios, but there is evidence that hypothetical judgments cannot accurately predict actual behavior. Here we addressed this issue by measuring how much money people will sacrifice to reduce the number of painful electric shocks delivered to either themselves or an anonymous stranger. Surprisingly, most people sacrifice more money to reduce a stranger’s pain than their own pain. This finding may help us better understand how people resolve moral dilemmas that commonly arise in medical, legal, and political decision making. Concern for the suffering of others is central to moral decision making. How humans evaluate others’ suffering, relative to their own suffering, is unknown. We investigated this question by inviting subjects to trade off profits for themselves against pain experienced either by themselves or an anonymous other person. Subjects made choices between different amounts of money and different numbers of painful electric shocks. We independently varied the recipient of the shocks (self vs. other) and whether the choice involved paying to decrease pain or profiting by increasing pain. We built computational models to quantify the relative values subjects ascribed to pain for themselves and others in this setting. In two studies we show that most people valued others’ pain more than their own pain. This was evident in a willingness to pay more to reduce others’ pain than their own and a requirement for more compensation to increase others’ pain relative to their own. This ”hyperaltruistic” valuation of others’ pain was linked to slower responding when making decisions that affected others, consistent with an engagement of deliberative processes in moral decision making. Subclinical psychopathic traits correlated negatively with aversion to pain for both self and others, in line with reports of aversive processing deficits in psychopathy. Our results provide evidence for a circumstance in which people care more for others than themselves. Determining the precise boundaries of this surprisingly prosocial disposition has implications for understanding human moral decision making and its disturbance in antisocial behavior.